(untitled) (Вестник КазНУ. Серия Востоковедения, 2016)
В статье рассматриваются поэтические особеннос- ти иранского поэта Моулави и его глубокие размыш- ления о человеке и бытие. Проблемы религии и Бога занимают особое место в творчестве поэта. Решение многих нравственных проблем Моулави связывает с любовью к Богу, Создателю. The article deals with the poetic features of the Iranian poet, Moulavi, and his deep thoughts about a human being and a life. In his works the poet focuses on religion and God aspects. Moulavi sees the solutions of many moral issues in the the love of God, the Creator.